Adaptive ambulance monitoring system using IOT. (December 2022) - Mahalakshmi, S.; Ragunthar, T.; Veena, N.; Sumukha, S.; Deshkulkarni, Pranav R.
Abstract: - With the increase in the number of automobiles in urban cities, the number of accidents has increased manifold. Hence, the need for ambulances is increasing at an alarming rate. In order to increase the survival rates of the patients, an efficient communication of ambulances with the hospital and routing of the ambulances at the signal posts is very essential. Hence, the proposed architecture is distributed in nature. The system not only provides effective communication between the ambulance and the hospital but also helps the ambulance send the signal to nearby traffic signal posts to open up so that the ambulance can easily pass through saving ample amounts of time. The signal posts use a camera to detect the incoming ambulance and open up that lane so that the ambulance need not spend much time waiting for the traffic to get cleared.